The Effect Of Job Stress And Workload On Employee Performance: The Moderating Role Of Work Environment Among Generation Z Outsourced Sales Generalis In PT Bank Mandiri (Persero) Tbk Area Bengkulu - Ameratul Fedhla; Amir Tengku Ramly; Eka Pariyanti (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study was motivated by the declining performance of Generation Z outsourced sales generalist employees PT Perdana Prima Bhakti Mandiri under the coordination of PT Bank Mandiri (Persero) Tbk Bengkulu Area, which is assumed to be influenced by job stress, workload, and work environment conditions. This research aims to analyze the effect of job stress and workload on employee performance with work environment as a moderating variable. The study employed a quantitative approach using a survey method involving 60 respondents selected through purposive sampling. Data were collected through structured questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings indicate that job stress significantly affects employee performance with a path coefficient of 0.479 and a p-value of 0.000, while workload significantly affects employee performance with a coefficient of 0.469 and a p-value of 0.000. The work environment significantly moderates the relationship between job stress and employee performance with a coefficient of 0.156 and a p-value of 0.041, and moderates the relationship between workload and employee performance with a coefficient of 0.197 and a p-value of 0.004. The study concludes that a supportive work environment strengthens employees’ adaptability in managing work pressure and workload.